2023
DOI: 10.1002/lary.30668
|View full text |Cite
|
Sign up to set email alerts
|

Residency Selection in Otolaryngology: Past, Present, & Future

Abstract: ObjectivesTo examine the otolaryngology residency selection process, including past experiences based on the medical literature and survey analysis of our present practices to generate recommendations for future selection system design.MethodsA mixed‐methods study, including a scoping review and a cross‐sectional survey, was completed. Four databases were assessed for articles on otolaryngology residency selection published from January 1, 2016 through December 31, 2020. A 36‐question survey was developed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Overapplication has many negative downstream effects 5 . Program directors are overwhelmed by applications, have difficulty discerning genuine interest from applicants, and overly weight imperfect screening metrics such as USMLE board scores 6 and medical school rankings. To keep up with the arms race, applicants face the financial and time consequences of applying to more and more programs each year with no improvement in the match rate 7 …”
Section: Introductionmentioning
confidence: 99%
“…Overapplication has many negative downstream effects 5 . Program directors are overwhelmed by applications, have difficulty discerning genuine interest from applicants, and overly weight imperfect screening metrics such as USMLE board scores 6 and medical school rankings. To keep up with the arms race, applicants face the financial and time consequences of applying to more and more programs each year with no improvement in the match rate 7 …”
Section: Introductionmentioning
confidence: 99%
“…Additional criteria or traits that can be employed to better differentiate between applicants using holistic review should be identified. 9 …”
mentioning
confidence: 99%